KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Bajari, Makarius; Su, lambertina; Lotte, Lucky Natalia (Cakrawala Management Business Journal, 2024)
The purpose of this study was to determine the effect of partial leadership, motivation and work discipline on employee performance at the Pasir Putih Health Center, Manokwari Regency. This type of research uses a quantitative approach with the type of associative problem. The sampling technique used the Slovin formula. The number of samples used was 120 employees at the Pasir Putih Health Center, Manokwaari Regency, the data analysis technique used multiple linear regression. The results of the study show that partially motivation does not show an influence on employee performance, while leadership and work discipline shows an influence on employee performance. Simultaneously significant effect on employee performance